Influências das tecnologias digitais no processo formativo: percepções de estudantes do ensino médio - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Inserted in a context that investigates Digital Technologies (DT) in Basic Education (EB), this research has as its central objective to identify the relationships that high school students establish with and from Digital Technologies and their influence on their training process. As an epistemological contribution, we adopt Pierre Bourdieu's theory of practice. We draw on the theoretical constructs of Pierre Bourdieu, Paulo Freire, and Pierre Lévy to discuss aspects related to Basic Education, Digital Technologies, and the social contexts in which our object is inserted. The corpus of this investigative study of a quali-quantitative nature, 408 high school students or technical education integrated to high school from four public institutions, located in the north of Paraná. Data were collected through an electronic questionnaire. The methodological assumptions include the association between Discursive Textual Analysis from the perspective of Moraes and Galiazzi (2016); Cluster Analysis from the perspective of Battaglia, Di Paola; Fazio (2016), and Graph Analysis inspired by the Theory of Social Representation from the perspective of Pereira (1997). As the main results of this study, we identified that the relationships that students establish with Digital Technologies are, for the most part, based on the consumption of media information. The pedagogical practices involved in the educational process, also influenced by the transmissivity unilateral relationships, find fertile ground in the traditional educational process, and, in this regard, contribute little in terms of qualitatively enhancing educational practices. In another perspective, we identified contributions to the students' learning process, in the peculiar pedagogical practices, those based on dialogue, interaction, interactivity, and collaborative process, aspects that excel in critical and, therefore, emancipatory education. It remains for us then the task of making this particular, the general in Basic Education. This is the challenge, this is our utopia!
Keywords: Tecnologias Digitais; Práticas pedagógicas; Ensino Médio; Educação crítica; Pierre Bourdieu; Digital Technologies; Pedagogical practices; High school; Critical education; Pierre Bourdieu; CNPQ::CIENCIAS HUMANAS::EDUCACAO